Tantangan Pendidikan Islam di Sekolah pada Era Disrupsi: Telaah Kritis terhadap Kurikulum, Kompetensi Guru, dan Karakter Peserta Didik - Yenni Yenni; Rudihartono Rudihartono; Nur Aisyah; Muh Iqbal Muhidin; Amaluddin Amaluddin (FKIP UNSULTRA, 2026)
The era of disruption is characterized by rapid technological change, social transformation, unlimited flows of information, and changing student characteristics. These conditions present complex challenges for Islamic education in schools because learning can no longer focus solely on the transfer of religious knowledge. It must also develop students who are adaptive, critical, morally grounded, and committed to Islamic values. This study aims to critically analyze the challenges of Islamic education in schools in the era of disruption by focusing on three main aspects: curriculum, teacher competence, and student character. This study employed a literature review method using a qualitative-descriptive approach. Data were obtained from scholarly journal articles, academic books, educational policy documents, and relevant research findings, particularly those published within the last five years. Data were analyzed through the stages of identification, selection, classification, interpretation, and synthesis of relevant sources. The findings reveal five main issues. First, the Islamic education curriculum faces challenges related to relevance and flexibility in responding to technological changes and the competency demands of the twenty-first century. Second, Islamic Religious Education teachers’ competencies need to extend beyond pedagogical and professional competencies to include digital competence, information literacy, and digital pedagogical skills. Third, technological transformation may shift the orientation of Islamic education if it is not accompanied by the strengthening of Islamic values and spirituality. Fourth, students’ character faces challenges related to a crisis of role models, instant culture, disinformation, and changing patterns of social interaction. Fifth, strengthening Islamic education requires synergy among an adaptive curriculum, competent teachers, exemplary conduct, school culture, families, and the ethical use of technology. Therefore, Islamic education in the era of disruption must move from an informative learning paradigm toward a transformative, humanistic, digitally responsive, and character-oriented educational paradigm.